Effect of an Electric Vehicle Promotion Policy on China’s Islands: A Case Study of Hainan Island - Xiao, Xu; Chen, Ziyue; Wang, Chan; Nie, Pu-yan (Frontiers in Energy Research, 2020)
Despite the abundant clean energy resources on islands, energy supply on the islands in many countries and regions still depends on high-voltage power grids in neighboring continents and high-cost fossil energy such as oil. In China, increasing demand for private gasoline vehicles calls for an abundant gasoline supply, which is harmful to the renewable energy transformation on Chinese islands. The promotion of electric vehicles offers a potential solution. However, on large islands with large populations, insufficient electricity supply restricts residents’ behavior, which has led to difficulties in promoting clean energy vehicles. To solve this problem, in 2019, the government formulated an 11-year plan to comprehensively promote clean energy vehicles from the energy supply side and user demand side to transform Hainan Island into a clean energy island. However, some predictions in the report are doubtful. As a result, this study takes Hainan Island in China as an example. Based on data on energy and electric vehicles, the greenhouse gas emissions and electricity demand of the transportation industry in Hainan Island under policy and non-policy scenarios are calculated using a generation substitution accounting model. Based on the results, this study evaluates the expected effect of Hainan Province’s 11-year plan to develop clean energy vehicles and compares the results with those in the report. Policy implications based on the results are also proposed. This study combines the island’s energy structure with the application of electric vehicles and expands the evaluation of government policies on the impact of large-scale energy transformation from the perspective of the energy supply chain. It also provides a reference for energy transformation on other large islands.